2023
DOI: 10.1111/cns.14332
|View full text |Cite
|
Sign up to set email alerts
|

Altered large‐scale individual‐based morphological brain network in spinocerebellar ataxia type 3

Shu Su,
Runhua Sha,
Haishan Qiu
et al.

Abstract: BackgroundAccumulating evidences indicate regional gray matter (GM) morphology atrophy in spinocerebellar ataxia type 3 (SCA3); however, whether large‐scale morphological brain networks (MBNs) undergo widespread reorganization in these patients remains unclear.ObjectiveTo investigate the topological organization of large‐scale individual‐based MBNs in SCA3 patients.MethodsThe individual‐based MBNs were constructed based on the inter‐regional morphological similarity of GM regions. Graph theoretical analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 13 , 14 This method has been widely used in many diseases, including attention‐deficit/hyperactivity disorder (ADHD), 15 autism spectrum disorder (ASD), 16 and spinocerebellar ataxia (SCA). 17 To the best of our knowledge, the use of individual‐level morphological network analysis to study the brain network changes in SMA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 This method has been widely used in many diseases, including attention‐deficit/hyperactivity disorder (ADHD), 15 autism spectrum disorder (ASD), 16 and spinocerebellar ataxia (SCA). 17 To the best of our knowledge, the use of individual‐level morphological network analysis to study the brain network changes in SMA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, these shortcomings can be complemented by the newly proposed individual‐level morphological similarity network method by using Kullback–Leibler divergence‐based similarity (KLDs) measurement 13,14 . This method has been widely used in many diseases, including attention‐deficit/hyperactivity disorder (ADHD), 15 autism spectrum disorder (ASD), 16 and spinocerebellar ataxia (SCA) 17 . To the best of our knowledge, the use of individual‐level morphological network analysis to study the brain network changes in SMA has not been reported.…”
Section: Introductionmentioning
confidence: 99%